I have been trying to solve this lagrange problem for an hour with no result. I can't seem to isolate any variable.

$$f(x,y) = y^2 -4xy +4x^2$$

With constraint:

$$x^2 + y^2 = 1$$

I have found $x$ to = $-\left(\frac{λ-4}{2}\right)^2 + 1$. Using the constraint $x$ is also equal to $\sqrt{1-y^2}$. This still leaves me with two unknowns. I have tried solving for lambda and setting them equal to each other and I end up with $x^2 = y^2-\frac{3xy}{2}$.

There are still two unknown variables here. I am not sure what I should be isolating to get an answer to work with.


I would say the most direct way to do this would be to but this into matrix form.

$f(x,y)= \mathbf x^T A \mathbf x$

That is $f(x,y)= \begin{bmatrix} x&y \end{bmatrix} \begin{bmatrix} 4&-2\\-2&1 \end{bmatrix}\begin{bmatrix} x\\y \end{bmatrix}$

And the eigenvalues:

$\lambda$ is an eigevalue and $\mathbf v$ is and eigenvector if

$A\mathbf v = \lambda \mathbf v\\ (A-\lambda I)\mathbf v = \mathbf 0\\ \det (A-\lambda I) = 0$

$A-\lambda I = \begin{bmatrix} 4-\lambda&-2\\-2&1-\lambda \end{bmatrix}\\ \det (A-\lambda I) = \lambda^2 - 5\lambda = 0$

$\lambda = 0,5$ which will be the min and the max. And the normalized eigenvalues are the coordiniates that maximise and minimize.

$\lambda = 0\\ A\mathbf v = \mathbf 0\\ \begin{bmatrix} 4&-2\\-2&1 \end{bmatrix}\mathbf v = 0\\ \mathbf v = \begin{bmatrix} 1\\2 \end{bmatrix}$

$\lambda = 5\\ (A-2I)\mathbf v = \mathbf 0\\ \begin{bmatrix} -1&-2\\-2&-4 \end{bmatrix}\mathbf v = 0\\ \mathbf v = \begin{bmatrix} -2\\1 \end{bmatrix}$

But that isn't Lagrange multipliers:

Before getting to far, notice:

$f(x,y) = (y-2x)^2$

$\forall x,y, f(x,y) \ge 0$

There is an $(x,y)$ pair that satisfies the constraint such that $f(x,y) = 0$

$(\frac {1}{\sqrt5},\frac {2}{\sqrt5}),(-\frac {1}{\sqrt5},-\frac {2}{\sqrt5})$

Method of Lagrange multipliers:

$F(x,y,\lambda) = (y-2x)^2 + \lambda(x^2+y^2 -1 )\\ \frac {\partial F}{\partial x} = -4(y-2x) + 2\lambda x = 0\\ \frac {\partial F}{\partial y} = 2(y-2x) + 2\lambda y = 0\\ $

Adding twice the second to the first we get

$2\lambda x + 4\lambda y = 0$

Either $\lambda = 0$ and $y = 2x.$ This is the minimum we found above.

$x = -2y$ must be our maximum. Plug it into the constraint ...

$(\frac{2}{\sqrt 5},-\frac {1}{\sqrt 5}),(-\frac{2}{\sqrt 5},\frac {1}{\sqrt 5})$

$f(\frac{2}{\sqrt 5},-\frac {1}{\sqrt 5}) = 5$

  • $\begingroup$ ok the answer is clearer now. I didnt have the partials factored and wasnt able to see the answer quickly as a result. How were you able to find the pair that satisfied the constraints without using lagrange multipliers, in the first portion? $\endgroup$ – Sergei Levashov Apr 19 '18 at 1:59
  • $\begingroup$ @SergeiLevashov I have detailed the alternate approach. $\endgroup$ – Doug M Apr 19 '18 at 2:09

You are given $f(x,y)= y^2- 4xy+ 4x^2$ with constraint $g(x, y)= x^2+ y^2= 1$. Then $\nabla f= <-4y+ 8x, 2y- 4x>$ and $\nabla g= <2x, 2y>$. The basic idea of the Lagrange multiplier method is that those two vectors are in the same direction- one is a multiple of the other: $<-4y+ 8x, 2y- 4x>= \lambda<2x, 2y>$. Equating the same components, we have the two equations $4x+ 8y= 2\lambda x$ and $2y- 4x= 2\lambda y$. Together with the constraint $x^2+ y^2= 1$ that gives three equations for the three unknowns x, y, and $\lambda$.

But a value for $\lambda$ is not necessary for this problem so a good way to solve these equations is to first eliminate $\lambda$ by dividing one of the first two equations by the other: $\frac{4x+ 8y}{2y- 4x}= \frac{2x+ 4y}{y- 2x}= \frac{x}{y}$. From that $y(2+ 4y)= x(y- 2x)$ so $2y^2+ 4xy= xy- 2x^2$, $2y^2+ 3xy+ 2x^2= 0$. Completing the square, $2(x^2+ (3/2)xy+ (9/16)y^2-$$(9/16)y^2)+ y^2= 2(x+ (3/4)y)^2- (9/8)y^2= 0$. x+ (3/4)y= (3/4)y$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.